Modelling as an Aid to Biomass Combustion in Plant Design - Michael R.I Purvis; Gilbert Lim; Susan A. Races; Carlita M. Salazar; Raymond Girard R. Tan; Stanley Santos (ASEAN Journal of Chemical Engineering, 2004)
Solid biomass materials are recognized as a sustainable energy source worldwide. In particular, lump biomass has considerable potential for exploitation as fuel in small- size underfeed stokers. The paper considers the design features of the underfeed stoker and its advantages in the burning of biomass. Some expe. i nental results are given to indicate the plant parameters to be modelled. An initial modelling approach is described for single-particle solid fuel combustion to predict flow patterns using the FLUENT Computational Fluid Dynamic (CFD) code. Predictions are compared against available experimental results showing reasonable qualitative and quantitative agreement. The paper concludes with information on the constraints on the modelling study and proposals for new work.